Commitments and challenges in participatory development: a Korean NGO working in Cambodia. Issue 7 (2nd October 2016) - Yang, Yunjeong
ABSTRACT: Despite their growing significance in the development field, academic research regarding development NGOs from emerging donors, such as South Korea, is almost non-existent. This study is based on a case study of LotusWorld, a Korean NGO, and its two recent projects conducted in Siem Reap, Cambodia. Based on interviews with Korean staff and with a group of villagers in the local community, the article examines how LotusWorld's vision and practices of participation have evolved from the first project to the second, as well as the challenges that they faced. Suggestions for further community participation are made for key actors.